Comparison of guidelines for the management of rectal cancer. Issue 6 (27th July 2018) - Luzietti, E; Pellino, G; Nikolaou, S; Qiu, S; Mills, S; Warren, O; Tekkis, P; Kontovounisios, C
Graphical Abstract: A comparison between NCCN, ESMO and JSCCR Guidelines is presented, concerning the treatment of rectal cancer, with an analysis and discussion of their discrepancies. Differences indicate areas for research Abstract: Background: Overall survival from rectal cancer has almost doubled over the last 20 years. Following recommendations in management guidelines plays some part in this, but the extent of discrepancies between them has not been evaluated. Methods: National Comprehensive Cancer Network (NCCN, USA), European Society for Medical Oncology (ESMO, Europe) and Japanese Society for Cancer of the Colon and Rectum (JSCCR, Japan) guidelines were examined and compared. These were chosen as representative of the countries with the highest incidences of rectal cancer and because no previous collaborations among societies were found. Results: Overall agreement among societies was found regarding the definition of total mesorectal excision as the surgical standard, the administration of adjuvant therapy for stage III disease, indications for surgical resection for metastases and/or recurrent disease, and the treatment of peritoneal disease. Discrepancies emerged, in particular between Western and Japanese guidelines. The most significant differences involved the endoscopic approach to early cancer, extended lymph node dissection, adjuvant treatment for patients with stage I and II disease, neoadjuvant chemotherapy, the specific management of metachronous disease, and restaging strategies. Conclusion: There are major discrepancies among guidelines. These differences should constitute topics for further research.